Poster 169: Prior Rotator Cuff Repair Is Not Associated with Worse Outcomes After Subsequent Superior Capsular Reconstruction: A Comparative Analysis. Issue 7 (30th July 2022) - Chao, Richard; Solomon, David; Vyas, Dharmesh; Curley, Andrew
Objectives: To compare the outcomes of two patient cohorts: (1) primary SCR and (2) SCR after failed rotator cuff repair. Methods: A retrospective review was performed of all patients who had a SCR at our institution from 2015 to 2020. Data was collected for patient demographics, prior rotator cuff surgery, comorbidities, and preoperative and postoperative range of motion, strength testing, visual analog scale (VAS) pain scores, Patient-Reported Outcomes Measurement Information System (PROMIS) 10 scores, American Shoulder and Elbow Surgeons (ASES) score, Brophy-Marx shoulder activity scale, and revision surgeries. Missing data points were excluded from analysis at that time point. Comparative analysis was used to assess for differences between patients that underwent an SCR only versus SCR after rotator cuff repair. Results: Fifty-four patients met inclusion criteria, consisting of 33 SCR only patients (61 ± 10 years, BMI 30 ± 6, 79% male) and 21 SCR after rotator cuff repair patients (59 ± 8 years, BMI 32 ± 5, 95% male). In the SCR only and SCR after rotator cuff repair groups, no significant difference was observed in age, BMI, gender, comorbidities, preoperative and postoperative range of motion, strength testing, VAS pain scores, PROMIS 10 scores, ASES score, Brophy-Marx shoulder activity scale, and revision surgeries (p>0.05). Conclusions: Similar outcomes were observed in patients who underwent primary SCR versus SCR after a failed rotator cuff repair, suggesting that surgeons should attempt to repair the rotator cuff at the index surgery if possible.